Suffrage in the Rural Province of Antioquia. The Manizales Cabildo elections of 1852 - Monsalvo Mendoza, Edwin Andres; Medina Montes, Mario (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The present study aims at examining the electoral process of 1852 in order to elect the chairs for the Manizales Cabildo. The article describes and analyzes the political electoral voting practices in a rural and recently founded society. The archival sources for this work are the electoral acts, electoral protocols, official correspondence and census of the Manizales Cabildo. This corpus allows for the construction of a typology of the suffragist, the assembly and elect chairs, as well as of voting rhythms during the 8 day assembly. The hypothesis is that, thanks to their condition as a direct elections with a public voting system, these elections allowed the economic elite (represented in the founders and members of the evaluation committees for the assignment of plots of land to new colonizers) to constitute itself as a political hierarchy through voting processes.